Case report: arteriovenous malformation in foot. Surgical management combined with scleroting agent - Rustina, Lusi; MT, Ivan Joalsen (Folia Medica Indonesiana, 2017)
Diagnosis and management of arteriovenous malformation (AVM) requires a multidisciplinary approach and includes the knowledge of the pathophysiology of the blood vessels. The incidence of vascular anomalies is rare, and they are mainly localized in the head or upper extremity. There are studies on AVM with dermatological manifestations. However, studies involving manifestations in foot are rare. The goal of this report is to provide diagnosis and treatment case of an 19 year-old boy with arterio-venous malformation of the foot. A 19-year-old Indonesian male presented with a chief complaint of a painful mass on his plantar medial right foot that had been present since his birth and had increased in size. Physical examination revealed a large plantar medial mass, with size ± 8 x 5 cm, slightly mobile, bluish, soft, and non-compressible. The mass was pulsatile on palpation and no bruit. The working diagnosis of this patient was AVM. MRI showed there was a punctat or nidus, granular hyperintense in the middle and pedis with a draining vein, and the mass was laying from subcutaneous and extended into muscular layer. Surgical management was performed. Excision of AVM in subcutaneous part was combined with injection of polidocanol 1% in muscular side. Tissue pathology results revealed AVM with no evidence of malignancy. Evaluation wounds after 2 days of operation: there was no bleeding, no signs of infection, pain was reduced. Four weeks after surgery, the patient slowly could bear his full weight on his foot, and the mass and local pain were totally reduced. Length of stay in hospitals was 4 days. This report described an unusual localization of an arteriovenous malformation. Arteriovenous malformation in foot is a challenging malformation that can be successfully managed with excision and sclerosing agents.